EXAMINATION OF ENTEROBIUS VERMICULARIS EGGS IN STUDENT OF SDN 12 LANGKAI PALANGKA RAYA IN 2025 - Ramdhani, Fitria Hariati; Al Hidayani; Khairul Iman (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Enterobius vermicularis is a small intestinal nematode that causes enterobiasis infection. This infection is most commonly found among elementary school–aged children. The aim of this study was to describe the microscopic findings of Enterobius vermicularis eggs among first- and second-grade students of SDN 12 Langkai, Palangka Raya City, in 2025. This research employed a descriptive approach, with specimen collection carried out using the anal swab technique. Samples were examined microscopically after staining with 5% eosin solution, and observations were performed under a light microscope using 10× and 40× objective lenses. The results showed that no eggs or larvae of Enterobius vermicularis were detected in any of the samples, indicating that all samples were negative. Based on these findings, it can be concluded that no cases of enterobiasis infection were found among the first- and second-grade students of SDN 12 Langkai, Palangka Raya City.